2008
DOI: 10.1007/s11120-008-9294-1
|View full text |Cite
|
Sign up to set email alerts
|

Fine tuning of the spectral properties of LH2 by single amino acid residues

Abstract: The peripheral light-harvesting complex, LH2, of Rhodobacter sphaeroides consists of an assembly of membrane-spanning alpha and beta polypeptides which assemble the photoactive bacteriochlorophyll and carotenoid molecules. In this study we systematically investigated bacteriochlorophyll-protein interactions and their effect on functional bacteriochlorophyll assembly by site-directed mutations of the LH2 alpha-subunit. The amino acid residues, isoleucine at position -1 and serine at position -4 were replaced by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 31 publications
(40 reference statements)
1
8
0
Order By: Relevance
“…This implies contributions of alanines at these positions to the overall stability of the protein fold. Interestingly, although impossible to verify statistically because of sample size, the rare occurrence of glycine in all critical positions and its complete exclusion from position −1 is noteworthy and consistent with our previous experimental data 37, 38. Our experiments revealed that placing glycine at position −1 in natural and model (B)Chl protein complexes significantly destabilized the complex, while other residues showed little effect.…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…This implies contributions of alanines at these positions to the overall stability of the protein fold. Interestingly, although impossible to verify statistically because of sample size, the rare occurrence of glycine in all critical positions and its complete exclusion from position −1 is noteworthy and consistent with our previous experimental data 37, 38. Our experiments revealed that placing glycine at position −1 in natural and model (B)Chl protein complexes significantly destabilized the complex, while other residues showed little effect.…”
Section: Resultssupporting
confidence: 90%
“…Interestingly, although impossible to verify statistically because of sample size, the rare occurrence of glycine in all critical positions and its complete exclusion from position −1 is noteworthy, and consistent with our previous experimental data. 37,38 Our experiments revealed that placing glycine at position −1 in natural and model (B)Chl protein complexes significantly destabilized the complex, while other residues showed little effect. One explanation for this glycine-specific effect at the (B)Chl-protein interface may be that the planar structure of the phorphyrin core is devoid of groups that could fill the void created by the absence of any side chain.…”
Section: Resultsmentioning
confidence: 73%
See 2 more Smart Citations
“…Ample factors related to the thermostability are discussed, amongst those are (i) optimizing and increasing the packing density by filling cavities in the protein structure (Silber et al 2008;Ishikawa et al 1993) and (ii) increased polar surface in comparison with non-polar surfaces. Comparisons between thermophile and mesophile proteins indicate that the thermophile proteins generally contain more charged residues and an increased number of salt bridges (e.g.…”
Section: Introductionmentioning
confidence: 99%